Extracorporeal shock wave therapy in the supportive care and rehabilitation of cancer patients - Crevenna, Richard (Support Care Cancer, 2019)
PURPOSE: Cancer patients sometimes show immobilizing musculoskeletal conditions which prohibit active exercise due to severe bodily pain. Therefore, before starting a rehabilitative exercise program, the pain has to be reduced to enable the patient to participate actively in the exercise program. Extracorporeal shock wave therapy (ESWT, the application of radial and/or focused shock waves with low or high energy) has been shown to be effective and efficient in the treatment of musculoskeletal disorders. However, one historical paradigm was the fact that, in the past, cancer was seen as a contraindication for the use of ESWT. METHODS: Clinical note to present indications, benefits, and contraindications of shock wave treatment in cancer patients. RESULTS: Malignant tumors in the treatment area have to be seen as a contraindication for the use of ESWT treatment. Cancer itself—in the form of the underlying disease—is not a contraindication for the treatment with radial and focused shock wave therapy with low or high energy. Plantar fasciitis and calcaneal spurs, calcified shoulder, tennis elbow or Achilles tendinopathy, and delayed healing and chronic wounds are typical approved standard indications for ESWT, and are allowed when the malignant tumor is not in the treatment area. There are also other musculoskeletal and non-musculoskeletal indications (e.g., myofascial syndrome, erectile dysfunction, polyneuropathy, and lymphedema) that are relevant for cancer survivors. These indications are recommended by the International Society for Medical Shockwave Treatment (ISMST) for “common empirically tested clinical use” and as exceptional indications/expert indications. CONCLUSION: ESWT is a safe and relevant modality for the supportive care and rehabilitation of cancer patients.